2011
DOI: 10.1017/s1368980011000012
|View full text |Cite
|
Sign up to set email alerts
|

Validation of self-reported folic acid use in a multiethnic population: results of the Amsterdam Born Children and their Development study

Abstract: Objective: To assess folic acid supplementation rates and validate the self-reporting of folic acid supplement use among pregnant women in a multiethnic cohort. Design: Secondary analysis of a prospective cohort study. Setting: Self-reported folic acid supplement use in the Amsterdam Born Children and their Development study cohort was compared with serum folate concentrations using non-parametric trend analysis and linear and logistic regression. Subjects: A total of 4234 pregnant women of various ethnic back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…Similarly, a nationally representative study of NZ adults found that FAcontaining supplement users had a 48 % higher mean serum folate concentration compared with non-users (49) . The correlation between reported FA supplementation dose and PF seen in the present study is also similar to that found in a Dutch study conducted in the early second trimester of pregnancy (r 0•49; P = 0•001) (50) .…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, a nationally representative study of NZ adults found that FAcontaining supplement users had a 48 % higher mean serum folate concentration compared with non-users (49) . The correlation between reported FA supplementation dose and PF seen in the present study is also similar to that found in a Dutch study conducted in the early second trimester of pregnancy (r 0•49; P = 0•001) (50) .…”
Section: Discussionsupporting
confidence: 90%
“…However, planning of pregnancy was strongly associated with supplement use before pregnancy regardless of ethnicity, which has also been observed in some other studies [11, 14, 15, 24] but not in all [13]. Interestingly, parous women were less likely to use folic acid supplements than nulliparous women both in our study and several previous studies [11, 1315, 18, 19, 24] although parous women should have heard about the benefits of supplement use during their previous pregnancy. Women who have previously delivered healthy children might trivialize the risks and be reluctant to follow recommendations on healthy behavior, as discussed by van Eijsden [13].…”
Section: Discussionsupporting
confidence: 89%
“…The most recent data on folic acid use in the Netherlands derive from studies in 2003-2004 and 1995-2005. However, the former study was conducted in one large city with many low-educated women and women of non-Western background (11) , and the latter study took place only in the northern part of the country (10) . The DELIVER study is a population-based cohort study conducted among a large number of women who received care in twenty midwifery practices across the Netherlands in 2009 and 2010.…”
mentioning
confidence: 99%